HOW TEACHERS IN AN INFORMAL ENGLISH TRAINING INSTITUTION TREAT YOUNG LEARNERS’ ORAL ERRORS - Faris, Ihsan Nur Iman; Budiarti, Dian (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
Corrective feedback needs to be used carefully to treat young learners’ oral errors as it should not inhibit learners from communicating. This study aims to investigate the use of corrective feedback strategies by informal English training center teachers in Bandung. Classroom observation and coding were used to collect and categorize data regarding errors committed by students and teachers’ use of corrective strategies. The study found that pronunciation errors (49%) were most frequently committed, followed by grammar (27%), vocabulary (20%), and the use of L1 (4%) errors. To treat those errors, the teachers apply corrective feedback strategies, which mostly were in the form of recast (46%) and elicitation (35%). Other corrective feedback strategies such as explicit correction (11%), metalinguistic feedback (6%), repetition (1%), and paralinguistic signal (1%) were found less frequently. This study suggests teachers consider several factors such as types of errors, learning factors, and learners’ factors when deciding the corrective feedback strategies.